Clay slurries analysis using inductively coupled plasma optical emission spectrometry with axial view configuration - Silva, C. S.; Nobrega, J. A.; Blanco, T. (Soc Brasileira Quimica, 2002)
The goal of this study was to evaluate the feasibility of direct introduction of clay slurries in an inductively coupled plasma optical emission spectrometer with axial view configuration. Calibration was performed using a certified reference material with a mean particle size of 13 mum (IPT 42) and the analytical curve was applied for quantification of two others reference materials (IPT 28 and IPT-32) and four samples. It was demonstrated that the analytical curve thus obtained was not completely suitable for IPT 28 and samples due to different mineralogical phases determined by X-ray diffraction. After considering this effect, it was possible for most elements to obtain results in agreement with certified values or with values obtained by a conventional technique at a 95% confidence level. It was demonstrated that the ICP-OES with axial view configuration did not present any incompatibility with the direct introduction of a complex inorganic suspension.
Keywords: clay slurries; inductively coupled plasma optical emission spectrometry; axial view configuration